Improving the quality of axisymmetrically drawn products using differentiated heating of the sheet blank's flange - Kulik, T. O.; Кулік, Т. О. (International Scientific Unity, 2025)
Undoubtedly, one of the most widely used processes of sheet metal stamping is the process of drawing and, in particular, axisymmetric drawing of cylindrical blanks without thinning and with thinning of the wall. The drawing ratio is one of such process schemes' main technical and economic indicators. Reducing the ratio ensures a decrease in the total number of transitions and intermediate annealings, which contributes to the expansion of the range of finished products, a reduction in the labour intensity of production and a decrease in the costs of its manufacture. However, reducing the drawing ratio will lead to an increase in tensile stresses in the dangerous section. The consequence of such an increase in stresses will be an increase in the probability of destruction of deformed blanks and, therefore, a decrease in the output coefficient of suitable metal products.